Development of a Distribution Channel for Coconut Products by Farmers in Nakhon Pathom Province - Chaitorn, Thun; Thitart, Phitphisut; Panichayakorn, Tanasarn (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The Development of a Distribution Channel for Coconut Products by Farmers in Nakhon Pathom Province aimed to study the distribution channel of selling coconut products of farmers in Nakhon Pathom province and to develop a channel for distribution of coconut products of farmers in Nakhon Pathom province. This research was qualitative research. Surveys and interviews, ten farmers in Nakhon Pathom province, were used as tools to collect data. The results of the study found that almost all farmers had offline distribution channel such as selling at a market or their houses. After farmers developed a sales channel through online platform, Facebook pages, they received 1,000 - 5,000 page views per day, and the number of orders continued to increase. Therefore, it helped farmers in Nakhon Pathom province to increase sales of coconut products by an average of 59.6 per cent per day. Article history: Received 24 March 2023 Revised 8 October 2023 Accepted 11 October 2023 SIMILARITY INDEX = 1.24 %